Comparison of life cycle assessment for different volume polyethylene packaging on the environment - Lazić Vera; Krkić Nevena; Šuput Danijela; Popović Senka (Journal on Processing and Energy in Agriculture, 2013)
In this paper, environmental impact of polyethylene tubes of different volumes: 30 mL and 100 mL was assessed using the life cycle assessment. The data were collected on the types and amounts of the materials and energy consumption in the process of packaging and distribution and inserted in the software GaBi 5. Total mass life cycle inventory was considerably lower for the smaller volume packaging. Breaking the inventory to the single flows, it was found that in both life cycles (polyethylene tubes of 30 mL and 100 mL) the highest contribution had the flows of fresh water consumption, emission of inorganic elements to the air and fresh water pollution with waste water flows. The highest contribution to all of these flows was shown to be production and consumption of diesel fuel. The results of this paper show that in analised case, more environmental friendly is the larger volume packaging.